Indigenous Knowledge and Forest Succession Management in the Brazilian Amazon: Contributions to Reforestation of Degraded Areas - Schmidt, Marcus Vinícius C.; Ikpeng, Yakuna Ullillo; Kayabi, Tariaiup; Sanches, Rosely Alvim; Ono, Katia Yukari; Adams, Cristina (Frontiers in Forests and Global Change, 2021)
The indigenous systems of agricultural and forest management in the Amazon are characterized by a deep knowledge of ecological processes, biodiversity and the use of fire. The influence of these systems on the distribution of biodiversity includes semi-domesticated and domesticated species and landscapes, which have led to extensive anthropogenic or cultural forests. However, in many places, the livelihoods of indigenous peoples are being transformed by the intensification of agriculture and by social, ecological and economic changes, putting at risk the sustainability of production systems and the security and food sovereignty of these peoples. In recent years, in the Xingu Indigenous Land (XIT), the productive systems and the form of occupation of the territories have changed, affecting the recovery of secondary forests during the fallow period. The increase in the number of fires has aggravated this situation, which has become more frequent in these areas due to the drier climate that has become prevalent in the region and the high rates of deforestation that have occurred in municipalities neighboring indigenous lands, especially in the headwaters of the region. Xingu river basin. We conducted a survey among the Kawaiwete (Tupi-Guarani) and Ikpeng (Karib-arara) peoples of XIT, in the state of Mato Grosso, Brazil. The main objective was to develop alternative forest management techniques based on indigenous and scientific knowledge more adapted to the new subsistence contexts, aiming at favoring forest regeneration in areas dominated by shifting agriculture. We seek to answer the following questions: (I) How do forests regenerate during the agricultural cycle? (II) What management techniques and traditional customs facilitate forest regeneration in order to maintain these systems in the long run? (III) Are there species that indicate secondary succession, soil recovery and fire vulnerability in these systems? (IV) Is the increase in the number of fires affecting the sustainability of these systems? Our results show that the most resilient local practices based on indigenous knowledge, such as the choice of forest areas already recovered for agricultural use, limits for cultivation and protection cycles, selection and attraction of seed dispersers can indicate ways to improve environmental management. of the XIT.